Involuntariness is the Name of the Debt Game (Notes on the Philippine Government's Debt Strategy) - Montes, Manuel (Kasarinlan: Philippine Journal of Third World Studies; Vol 3 No 3 (1988), 2007)
This article discusses the following points concerning the Aquino government's strategy in managing its significant debt service burden: the importance of renegotiating the foreign debt restructuring agreements, so that the Philippines will not be considered in default; the limitations of the government in debt negotiations; and the infeasibility of an accommodating negotiating stance. On the matter of the government's role in determining the strategy of debt payment, it is emphasized that the government can only determine the Philippine position, not the overall outcome. It should not internalize the interest of foreign creditors, which may be prevented from happening by instituting a commission whereby citizens that will be greatly affected by the government's debt strategy will have a power of representation commensurate with the sacrifices they might be called to undertake. The strategy on foreign debt, which primarily involves a political decision, must reflect the preparedness of the country to accept hardship in exchange for benefits from its creditors.